Environmental Costs And Its Implication On The Returns On Investment: An Evaluation Of Selected Manufacturing Companies In Nigeria (Global Journal of Management and Business Research, 2012)
This study examines environmental costs and its implication on the returns on investment. At various national levels are government regulations, society, pressure groups and green consumer pressure; developments reawakening corporate attention to strategic and competitive role of environmental responsibility for corporate survival. However within the developing nations, the understanding is somewhat different mainly because of weak government regulations and lack of organized pressure groups and consumer awareness to influence corporate behaviour. Data were collected from both primary and secondary sources and also analyzed using the ordinary least square technique. The study revealed that investment in social and environmental responsibilities such as Employee Health and Safely (EHS), Waste Management (WM) and Community Development (CD) are related to improved return on investment of the environmentally responsible firms. Additionally, the study also revealed that with sustainable business practice, there is a decrease in the amount paid in fines and penalties to individuals and the government for environmental offences and its compensation to the community. Conclusively, money expended in settling disputes could be applied to enhance corporate liquidity and management is better able to plan and make decisions when it is not engrossed in disputes. The act of managing and production per se is optimal when an enabling serene atmosphere is in place. The study therefore recommended that Environmental Regulatory Authority should compel manufacturing companies to disclose environmental cost in their financial statement and Environmental management accounting should be incorporated into the traditional accounting systems of manufacturing companies.
Keywords: Environmental practice; Environmental responsibilities; Social responsibilities; Waste management; Community development; Employee health and safety